Primary cilia in the mature brain: emerging roles in Alzheimer’s disease pathogenesis - Huang, Alexis Shiying; Li, Amy Sze Man; Hor, Catherine Hong Huan (Frontiers in Cell and Developmental Biology, 2025)
Primary cilia are microtubule-based structures that resemble antennae and function as sensory organelles. Dysfunction of primary cilia has been linked to various age-related conditions. Alzheimer’s disease, which affects more than 38.5 million individuals worldwide, is a prominent neurodegenerative disorder, with aging being its most significant risk factor. In this review, we provide an overview of current findings on the role of primary cilia in the mature brain and the mechanisms by which alteration of primary cilia may influence the progression of Alzheimer’s disease. Growing evidence reveals that primary cilia in the mature brain play dynamic roles in cell type, region, and age-dependent manners. In Alzheimer’s disease, anomalies in primary cilia functions and morphology are closely associated with key pathologies. However, the exact mechanisms remain unclear. Future studies on neuronal and glial cilia dynamics during aging and neurodegeneration are essential to explore their potential as therapeutic targets.